Comparative genomic hybridization detects novel amplifications in fibroadenomas of the breast - Ojopi, EPB; Rogatto, Silvia Regina [UNESP]; Caldeira, JRF; Barbieri-Neto, J.; Squire, J. A. (Wiley-Blackwell, 2001)
Comparative genomic hybridization analysis was performed for identification of chromosomal imbalances in 23 samples of fibroadenomas of the breast. Chromosomal gains rather than losses were a feature of these lesions. Only two cases with a familial and/or previous history of breast lesions had gain of 1q or 16q as the sole abnormality. The most frequently overrepresented segments were 5p14 (10/23 cases), 5q34-qter (6/23 cases), 13q32-qter (6/23 cases), 10q25-qter (5/23 cases), and 18q22 (4/23 cases). Some of these regions have previously been associated with breast carcinoma, but this study indicates that gain of these regions can also occur in benign breast lesions. Our findings may provide a basis for conducting further investigations to locate and identify genes associated with proliferation that may be involved in the early steps of tumorigenesis of the breast. (C) 2001 Wiley-Liss, Inc.